Binge eating behaviours and food cravings in women with Polycystic Ovary Syndrome. (1st February 2017) - Jeanes, Y.M.; Reeves, S.; Gibson, E.L.; Piggott, C.; May, V.A.; Hart, K.H.
Abstract: Polycystic Ovary Syndrome (PCOS), the most common endocrine condition in women, is often anecdotally associated with binge eating behaviours and food cravings; however there is a paucity of research. This study aimed to report the prevalence of binge eating and food cravings and their relation to obesity risk in women with PCOS. Participants completed an online survey including the Bulimia Investigatory Test, Edinburgh, Food Cravings-Trait Questionnaire and the Three Factor Eating Questionnaire revised-18. The study included obese (n = 340), overweight (n = 70) and lean (n = 45) women with PCOS and lean healthy women (n = 40). Sixty percent of obese women with PCOS were categorised with binge-eating behaviour, with 39% presenting with clinically significant behaviour. Obese women with PCOS presented with high mean food cravings-trait scores (131.6 ± 28.9) that were significantly greater compared with lean (114.0 ± 34.9) and overweight women with PCOS (120.1 ± 29.5; p < 0.001). Multiple regression exploring relations between eating styles and adiposity explained 57% of the variance in binge eating symptom scores in women with PCOS (F = 130.4; p < 0.001, n = 463): significant predictors were food cravings total score (beta = 0.53; p < 0.001), emotional eating score (beta = 0.18; p < 0.001), body mass index (beta = 0.11; p < 0.001) and uncontrolled eating score (beta = 0.009; p = 0.02). Compared with lean healthy women, lean women with PCOS exhibited significantly higher binge eating symptom scores (10.9 ± 7.8 versus 7.4 ± 6.0; p < 0.05), though similar total food craving scores (114.0 ± 34.9 versus 105.6 ± 26.6: NS). This study is the largest, to date, to robustly report that a high proportion of women with PCOS exhibit binge eating behaviours. We recommend screening women with PCOS for binge eating behaviours to help inform the choice of weight management approach for this clinical population.